A comparative examination of the extent to which the South African and the English legal systems recognize the defence of provocation in homicide cases - Ackermann, Leon Keith (Not Specified, 2021)
On charges of murder or assault, it often appears that the accused's aggression was immediately preceded by provocative behaviour e.g. taunts or insults by the victim which induced anger or rage in the accused and which gave rise to his aggression. The present study aims to address the question whether, in South African law, a defence is available to an accused in such cases. Since the issue of provocation in South African law usually arises in homicide cases, this study will be restricted to such cases. It will be shown that, during the past couple of decades, the South African law relating to provocation has undergone significant development. In 1925, the Appellate Division declared s 141 of the Native Territories Penal Code to be an accurate reflection of the South African law relating to provocation. In terms of this section, provocation could operate as a partial defence on a charge of murder: where an accused successfully raised the defence he would be convicted of culpable homicide. Recently, however, it has become clear that provocation may operate as a complete defence, resulting in an accused leaving the court as a free person. It will be argued that the above development reflects a general shift in our law, starting in the 1950's, from a policy-based to a principle-based approach to criminal liability.